Morphology is Relevant for the Written Form of Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The main areas of linguistics in general focus on the structure of language at different "scales". Morphology is considered to work on a larger scale than phonology, which explores categories of speech sounds that differ in spoken language, and thus may account for the difference between a morpheme and another. In contrast, syntax deals with the next largest scale and studies how words, in turn, form phrases and sentences. Morphological typology is a separate field that classifies languages based on the morphological features they exhibit.